BREWING WITH BUCKWHEAT AND SORGHUM: IMPACT ON BEER QUALITY - MARIUS EDUARD CIOCAN; ROZÁLIA VERONIKA SALAMON; ÁGOTA AMBRUS; GEORGIANA GABRIELA CODINĂ; ANCUȚA CHETRARIU; ADRIANA DABIJA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
n the process of obtaining gluten-free beer, various non-conventional raw materials were used. Some of these have shown real potential in obtaining quality finished products appreciated by consumers. In addition to health issues, several factors also play a role in the choice of these raw materials, one of which is the climate changes that are occurring around the globe. The paper summarizes our own research on the use of two of these non-conventional materials, buckwheat and sorghum, in unmalted form in the technological process of obtaining beer at microbrewery equipment. Through the research carried out, it was aimed to establish optimal conditions for mashing-saccharification and fermentation-aging processes that would lead to a quality finished product. The best results in terms of sensory and physico-chemical characteristics were achieved by beer obtained from 50 % unmalted buckwheat and 50 % unmalted sorghum.